Analytical approaches for lipidomics and its potential applications in neuropsychiatric disorders. (3rd October 2017) - Sethi, Sumit; Hayashi, Mirian A.; Sussulini, Alessandra; Tasic, Ljubica; Brietzke, Elisa
Abstract: Objectives : In this review, the authors discuss an overview of lipidomics followed by in-depth discussion of its application to the study of human diseases, including extraction methods of lipids, analytical techniques and clinical research in neuropsychiatric disorders. Methods : Lipidomics is a lipid-targeted metabolomics approach aiming at the comprehensive analysis of lipids in biological systems. Recent technological advancements in mass spectrometry and chromatography have greatly enhanced the development and applications of metabolic profiling of diverse lipids in complex biological samples. Results : An effective evaluation of the clinical course of diseases requires the application of very precise diagnostic and assessment approaches as early as possible. In order to achieve this, "omics" strategies offer new opportunities for biomarker identification and/or discovery in complex diseases and may provide pathological pathways understanding for diseases beyond traditional methodologies. Conclusions : This review highlights the importance of lipidomics for the future perspectives as a tool for biomarker identification and discovery and its clinical application.